Benign Familial Convulsions - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Results of linkage analysis between benign infantile familial convulsions (BIFC) and two linked DNA markers, D20S19 and D20S20, in 52 members from eight BIFC pedigrees are reported from centers in Montpellier and Paris, France, and Rome and Treviso, Italy.